The association of sexual frequency with cardiovascular diseases incidence and all-cause mortality - Tian-Qi Teng; Jing Liu; Meng-Meng Wang; De-Gang Mo; Rui Chen; Jia-Chao Xu; Zi-Han Dong; Ning Zhang; Hai-Chu Yu (Scientific Reports)
Abstract Sexual activity exists in a complex relationship with human health. This study aims to elucidate the correlation between the sexual frequency and the incidence of cardiovascular diseases (CVD) and all-cause mortality among young and middle-aged adults of the United States. We analyzed 17,243 participants from the National Health and Nutrition Examination Survey(NHANES)(2005–2016), comparing CVD incidence and all-cause mortality risks across sexual frequencies using multivariable Logistic and Cox regression models. Kaplan-Meier curves assessed survival probability stratified by sexual frequency, and a restricted cubic spline regression examined the nonlinear relationship between sexual frequency, CVD and survival status. We also established a nomogram and validated it by ROC and calibration curves. Over a median follow-up period of 106 months, 443 patients (2.57%) died. After adjusting for confounders, sexual frequency was found to be associated with CVD incidence and all-cause mortality among young and middle-aged individuals. Those with sexual acts less than 12 times/year faced the highest risks of CVD incidence and all-cause mortality, as frequency increased, the risks gradually decreased, reaching a nadir at approximately 52–103 times/year, but then a negative correlation began to emerge. A nomogram predicting survival rates based on sexual frequency achieved ROC areas of 0.782, 0.807, and 0.803 for 3, 5, and 10 years, with a calibration curve matching the ideal generally. Sexual frequency was associated with the incidence of CVD and all-cause mortality among young and middle-aged adults. Both excessive and infrequent sexual frequency may be detrimental to health.